MAKNA NILAI BUDAYA GREBEG SYAWAL DI YOGYAKARTA DAN SURAKARTA - Tazkyatunnisa, Hasna (Program Studi Sejarah Peradaban Islam Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2024)
The Grebeg Syawal tradition in Yogyakarta and Surakarta is a cultural heritage that is full of symbolic values ​​and deep meaning. This tradition is carried out every 1 Shawwal as a form of gratitude for the end of the month of Ramadan. This celebration takes place on Shawwal 1, coinciding with Eid al-Fitr, and involves a mountain procession filled with agricultural products. This researcher aims to explore the meaning and cultural values ​​contained in the Grebeg Syawal tradition in the Yogyakarta and Surakarta Palaces. The method used in this research is descriptive qualitative. The data source used in this research is the informant, namely the courtiers of the Surakarta palace. This research data is in the form of interview notes regarding the meaning and cultural values ​​of Grebeg Syawal in Yogyakarta and Surakarta. The technique used in this research is interviews. The results of this research conclude that this tradition is not only an expression of gratitude to God for the end of Ramadan, but also as a form of alms and respect for society.